PENGARUH PENGETAHUAN LINGKUNGAN DAN KEPEDULIAN LINGKUNGAN TERHADAP SIKAP DAN NIAT BELI PRODUK HIJAU “THE BODY SHOP” DI KOTA DENPASAR - Rini, Ayu Stia; Sukaatmadja, I Putu Gde; Giantari, I Gst. Ayu Kt. (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.06.NO.01.TAHUN 2017, 2016)
The Body Shop is a manufacturing company and global retail that produce toiletries and beauty products for men and women who apply the concept of green marketing and green business. The level of knowledge and concern began to grow on the environment spur companies to develop the program in providing solutions to environmental problems in order to improve attitude and purchase intention.This study aims to explain the effect of environmental knowledge and environmental concern on attitude and purchase intention, and explain the effect of attitude on purchase intention ofThe Body Shopgreen products in Denpasar. The sample used there are 150 respondents with purposive sampling technique. The data analysis technique used is Structural Equation Modelling (SEM) analysis technique. The results of analysis show that environmental knowledge and environmental positive and significantly effect on attitude and purchase intention, and attitude positive and significantly effect on purchase intention of The Body Shop green products in Denpasar.
Keywords: environmental knowledge, environmental concern, attitude, purchase intention, the bodyshop